The First Practical Additive-Free 1,4-Conjugated Alkylation of Fluoroalkylated Electron-Deficient Olefins with Various Organozinc Reagents - Morigaki, Atsunori; Miyabe, Tomotsugu; Tsukade, Kazuki; Arimitsu, Satoru; Ishihara, Takashi; Konno, Tsutomu (Synthesis, 2013)
1,4-Conjugated alkylation of fluoroalkylated olefins with organozinc reagents, such as RZnI and R2Zn, was conducted smoothly to give the corresponding products in moderate yields without the use of either transition metals or Lewis acids. This reaction protocol allows not only a wide range of alkyl groups but also electron-withdrawing groups to be incorporated as 1,4-conjugated adducts.
Keywords: 1,4-conjugated alkylation; organozinc reagents; trifluoromethyl; electron-deficient olefin